HMB Improves Lipid Metabolism of Bama Xiang Mini-Pigs via Modulating the Bacteroidetes-Acetic Acid-AMPKα Axis - Zheng, Jie; Zheng, Changbing; Song, Bo; Guo, Qiuping; Zhong, Yinzhao; Zhang, Shiyu; Zhang, Lingyu; Duan, Geyan; Li, Fengna; Duan, Yehui (Frontiers in Microbiology, 2021)
Here, we used Bama Xiang mini-pigs to explore the effects of different dietary β-hydroxy-β-methylbutyrate (HMB) levels (0, 0.13%, 0.64% or 1.28%) on lipid metabolism of adipose tissue. Results showed that HMB decreased the fat percentage of pigs (linearly, P < 0.05), and the lowest value was observed in the 0.13% HMB group. Moreover, the colonic acetic acid concentration and the relative Bacteroidetes abundance were increased in response to HMB supplementation (P < 0.05). Correlation analysis identified a positive correlation between the relative Bacteroidetes abundance and acetic acid production, and a negative correlation between fat percentage and the relative Bacteroidetes abundance or acetic acid production. HMB also upregulated the phosphorylation (p) of AMPKα, Sirt1, and FoxO1, and downregulated the p-mTOR expression. Collectively, these findings indicate that reduced fat percentage in Bama Xiang mini-pigs could be induced by HMB supplementation and the mechanism might be associated with the Bacteroidetes-acetic acid-AMPKα axis.